Exploiting Heterogeneity for Tail Latency and Energy Efficiency - Haque, Md E.; He, Yuxiong; Elnikety, Sameh; Nguyen, Thu D.; Bianchini, Ricardo; McKinley, Kathryn (Proceedings of the International Symposium on Microarchitecture (MICRO), 2017)
Interactive service providers have strict requirements on high-percentile (tail) latency to meet user expectations. If providers meet tail latency targets with less energy, they increase profits, because energy is a significant operating expense. Unfortunately, optimizing tail latency and energy are typically conflicting goals. Our work resolves this conflict by exploiting servers with per-core Dynamic Voltage and Frequency Scaling (DVFS) and Asymmetric Multicore Processors (AMPs). We introduce the Adaptive Slow-to-Fast scheduling framework, which matches the heterogeneity of the workload — a mix of short and long requests — to the heterogeneity of the hardware — cores running at different speeds. The scheduler prioritizes long requests to faster cores by exploiting the insight that long requests reveal themselves. We use control theory to design threshold-based scheduling policies that use individual request progress, load, competition, and latency targets to optimize performance and energy. We configure our framework to optimize Energy Efficiency for a given Tail Latency (EETL) for both DVFS and AMP. In this framework, each request self-schedules, starting on a slow core and then migrating itself to faster cores. At high load, when a desired AMP core speed s is not available for a request but a faster core is, the longest request on an s core type migrates early to make room for the other request. Compared to per-core DVFS systems, EETL for AMPs delivers the same tail latency, reduces energy by 18% to 50%, and improves capacity (throughput) by 32% to 82%. We demonstrate that our framework effectively exploits dynamic DVFS and static AMP heterogeneity to reduce provisioning and operational costs for interactive services.